Sculpting MHC class II–restricted self and non‐self peptidome by the class I Ag‐processing machinery and its impact on Th‐cell responses. Issue 5 (5th March 2013) - Spencer, Charles T.; Dragovic, Srdjan M.; Conant, Stephanie B.; Gray, Jennifer J.; Zheng, Mu; Samir, Parimal; Niu, Xinnan; Moutaftsi, Magdalini; Van Kaer, Luc; Sette, Alessandro; Link, Andrew J.; Joyce, Sebastian
<x xml:space="preserve">Abstract</x> It is generally assumed that the MHC class I antigen (Ag)‐processing (CAP) machinery — which supplies peptides for presentation by class I molecules — plays no role in class II–restricted presentation of cytoplasmic Ags. In striking contrast to this assumption, we previously reported that proteasome inhibition, TAP deficiency or ERAAP deficiency led to dramatically altered T helper (Th)‐cell responses to allograft (HY) and microbial (Listeria monocytogenes) Ags. Herein, we tested whether altered Ag processing and presentation, altered CD4+ T‐cell repertoire, or both underlay the above finding. We found that TAP deficiency and ERAAP deficiency dramatically altered the quality of class II‐associated self peptides suggesting that the CAP machinery impacts class II–restricted Ag processing and presentation. Consistent with altered self peptidomes, the CD4+ T‐cell receptor repertoire of mice deficient in the CAP machinery substantially differed from that of WT animals resulting in altered CD4+ T‐cell Ag recognition patterns. These data suggest that TAP and ERAAP sculpt the class II–restricted peptidome, impacting the CD4+ T‐cell repertoire, and ultimately altering Th‐cell responses. Together with our previous findings, these data suggest multiple CAP machinery components sequester or degrade MHC class II–restricted epitopes that would otherwise be capable of eliciting functional Th‐cell responses.